Relationship between Tension-Type Headache and Quality of Sleep, Excessive Daytime Sleepiness, and Fatigue Syndrome among Healthcare Workers during COVID-19 - Pepi Budianto; Stefanus Erdana Putra; Muhammad Hafizhan; Fauzi Novia Isnaening Tyas; Astrida Fesky Febrianty; Hanindia Riani Prabaningtyas; Diah Kurnia Mirawati; Rivan Danuaji; Subandi Subandi (Universitas Islam Bandung, 2021)
Coronavirus disease 2019 (COVID-19) is an infectious disease that was later declared a pandemic. During a pandemic, excessive workloads cause an increase in physical symptoms, such as tension-type headaches, in medical personnel. Tension-type headache (TTH) is associated with decreased sleep quality which will lead to excessive daytime sleepiness (EDS) and fatigue syndrome. This study aims to determine the relationship between TTH and sleep quality, EDS, and fatigue syndrome in medical personnel during the pandemic. This study is a cross-sectional study conducted on health workers at Sebelas Maret University Hospital, Surakarta, Indonesia in March–August 2020. The relationship between TTH and three other variables was analyzed using the Spearman correlation test. Multiple logistic regression analysis was used to calculate the odds ratio (OR) of headache associated with the covariate. The Kruskal-Wallis test was used to compare sleep quality, EDS, and fatigue syndrome in the TTH, non-TTH headache, and control groups. There were 120 respondents (mean age 30.93±12.48) in this study. The Spearman correlation test found a weak positive correlation between TTH and the three dependent variables. OR sleep quality, EDS, and fatigue syndrome with the incidence of TTH respectively 2.33 (95% CI=1.18–5.11, p<0.001); 2.52 (CI 95%=1.17–4.79, p=0.001), and 4.46 (95% CI=2.71–7.69, p<0.001). The Kruskal-Wallis test showed that the TTH group had poorer sleep quality and more frequent EDS and fatigue syndrome. There is a significant relationship between TTH and sleep quality, EDS, and fatigue syndrome in medical personnel during the pandemic. HUBUNGAN NYERI KEPALA TIPE TEGANG DENGAN KUALITAS TIDUR, RASA KANTUK BERLEBIHAN DI SIANG HARI, DAN SINDROM KELELAHAN PADA TENAGA MEDIS SELAMA COVID-19Coronavirus disease 2019 (COVID-19) merupakan penyakit menular yang kemudian dinyatakan sebagai pandemi. Selama pandemi, beban kerja yang berlebihan menyebabkan peningkatan gejala fisik, seperti nyeri kepala tipe tegang (tension-type headache) pada tenaga medis. Tension-type headache (TTH) dikaitkan dengan penurunan kualitas tidur yang akan menyebabkan rasa kantuk berlebihan di siang hari (excessive daytime sleepiness, EDS) dan sindrom kelelahan. Penelitian ini bertujuan mengetahui hubungan TTH dengan kualitas tidur, EDS, dan sindrom kelelahan pada tenaga medis selama pandemi. Penelitian ini merupakan studi potong lintang yang dilakukan pada petugas kesehatan di RS Universitas Sebelas Maret, Surakarta, Indonesia pada Maret–Agustus 2020. Hubungan antara TTH dan tiga variabel lainnya dianalisis menggunakan uji korelasi Spearman. Analisis regresi logistik ganda digunakan untuk menghitung odds ratio (OR) nyeri kepala yang terkait dengan kovariat. Uji Kruskal-Wallis digunakan untuk membandingkan kualitas tidur, EDS, dan sindrom kelelahan pada kelompok TTH, nyeri kepala non-TTH, dan kontrol. Terdapat 120 responden (rerata usia 30,93±12,48). Uji korelasi Spearman menemukan korelasi positif lemah antara TTH dan tiga variabel terikat. OR kualitas tidur, EDS, dan sindrom kelelahan dengan kejadian TTH secara berurutan 2,33 (IK 95%=1,18–5,11; p<0,001); 2,52 (IK95 %=1,17–4,79; p=0,001); dan 4,46 (IK 95%=2,71–7,69; p<0,001). Uji Kruskal-Wallis menunjukkan bahwa kelompok TTH memiliki kualitas tidur yang lebih buruk dan lebih sering mengalami EDS, serta sindrom kelelahan. Terdapat hubungan yang signifikan TTH dengan kualitas tidur, EDS, dan sindrom kelelahan pada tenaga medis selama pandemi.